APPLICATION OF DIGITAL DESIGN OF TOURISM CENTRE OF SENDURO IN BROMO - TENGGER - SEMERU NATIONAL PARK, INDONESIA - Oktafiana, Brina; Tjandra, Cynthia; Tanuwidjaja, Gunawan; Wijaya, Elvina Shanggrama; Adiasih, Priskila (Border: Jurnal Arsitektur, 2022)
Instagram able places is a new trend before the Covid-19 pandemic. The theory of Instagram able places has not yet developed in the Architectural field. Several business-related studies have proposed the use of social media, especially Instagram, to attract tourists to attractions. However, Instagram's design approach is only used by creating new building structures that alienate local ecology and dim cultural values. The Senduro Tourism Centre is used as an example of using Instagram for sustainable design at the tourism gate of Bromo Tengger Semeru National Park. The design of the Senduro Tourism Centre is carried out in such a way as to be able to move the economy of the tourism sector of Lumajang Regency in the pandemic era while maintaining the preservation of its natural and cultural assets to be sustainable. The Hindu-SacredProfane (Tri-Mandala) zoning, and a sustainable design approach, are also used to ensure the sustainable tourism activities of Senduro. As a result, using digital design tools, we are able to process and present elements of the natural and cultural landscape in an attractive perspective through the design of the Senduro Tourism Centre scheme. In the future, Instagram's design approach can be used more sustainably in tourist attractions in Indonesia.